2012
DOI: 10.5588/ijtld.11.0232
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' attitudes towards self-treatment of latent tuberculosis [Short communication]

Abstract: We conducted a cross-sectional study to assess physicians' attitudes towards self-treatment of latent tuberculosis infection (LTBI) based on real-time responses related to actual purified protein derivative (PPD) results, in addition to using hypothetical situations for those who were PPD-negative. We also obtained information on physicians' recommendations for their patients to treat this condition. Although the physicians claimed to recommend optimal treatment to their patients, the majority of them had diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…This behaviour was similar to that in a previous survey [6], in which compliance was even lower, with only about 25% of physicians who were indicated for LTBI treatment completing it.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…This behaviour was similar to that in a previous survey [6], in which compliance was even lower, with only about 25% of physicians who were indicated for LTBI treatment completing it.…”
supporting
confidence: 70%
“…
Although the incidence of tuberculosis (TB) has increased in healthcare workers (HCWs) [1][2][3], several studies have shown that HCWs are not compliant with screening and/or preventive measures [4][5][6][7]. For example, a Portuguese study found that the estimated TB incidence was three-to seven-fold higher in HCWs than in the general population [8].
…”
mentioning
confidence: 99%
“…Physicians seem to be sceptical about taking treatment for LTBI. A US study showing that only 25% of physicians with evidence of LTBI had actually received treatment for LTBI [36]. It is possible that physicians’ reluctance to accept treatment of LTBI themselves is the reason for the decreased likelihood that they will offer this treatment to other health care workers.…”
Section: Discussionmentioning
confidence: 99%
“…This social support focused on risk factors for non-adherence to preventive therapy such as being female and/or belonging to a marginalised group, 43 , 81-83 age, 83,84 illegal drug use, 46 homelessness, 47 alcohol misuse, 85 and TB-affected families' and individual's own knowledge, attitudes and perceptions. 80,86 Although our group had originally applied for funding to perform a 2×2 factorial study evaluating economic support versus social support and socioeconomic support versus standard of care, the sample size required was prohibitive and that application was not funded. The final funded study design of this CRESIPT pilot study did not allow analysis of the differential impact of the social support component and the economic support component of cash transfers on access to preventive therapy and TB cure rates.…”
Section: Discussionmentioning
confidence: 99%